Estudio Geométrico y Estructural de la vía Aldea - Unión Lojana desde la abscisa 0+000 hasta 5+400 Km del cantón Marcabeli, Provincia de El Oro - Moreira Cordova, Mónica Katherine (2015)
The route is Lojana Village- Union under unfavorable conditions, causing economic losses for the inhabitants of these areas, making difficult the normal movement of their products, mobilizing them, private income and services for the delay and other factors. That is why this project aims to improve road conditions, providing comfort, safety and comfort optimizing time and resources to people and other users either to transport their products, goods or transfer of people from one place to another, meeting the best geometric and structural characteristics according to MTOP standards. For the preparation of Geometric Design, Structural package Environmental Impact Study and Analysis of Budget employ the results of field and laboratory, such as traffic counts, site topography, soil studies of the respective test pits and analysis asphalt mixture. Village- Union Lojana is a way of IV ORDER IN LAND Hilly, with a design speed of 40 km / h, has a length of 5415 meters, has a track width of 7.20 meters. This titling project has been reviewed and approved and at the same time can make the respective procedures for the execution of the work.